2017
DOI: 10.1111/fwb.12906
|View full text |Cite
|
Sign up to set email alerts
|

Native brook trout and invasive rainbow trout respond differently to seasonal weather variation: Spawning timing matters

Abstract: Salmonids have been introduced globally, and native and invasive salmonids co‐exist in many regions. However, their responses to seasonal weather variation and global climate change are poorly known. The aim of this study was to compare effects of inter‐annual variation in seasonal weather patterns on native brook trout (BKT) (Salvelinus fontinalis) versus invasive rainbow trout (RBT) (Oncorhynchus mykiss) abundance using summer electrofishing data (May through September) spanning 28 years in the Great Smoky M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 78 publications
(113 reference statements)
1
26
0
Order By: Relevance
“…Moreover, we found that in four of the seven species hydrological conditions scored the highest importance during the pre‐spawning period (Table ). Therefore, our finding likely supports that it is important for improving model performance to include not only antecedent environmental factors but also their occurrence times in association with the dispersal phase of the life‐history stages (Kanno et al ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, we found that in four of the seven species hydrological conditions scored the highest importance during the pre‐spawning period (Table ). Therefore, our finding likely supports that it is important for improving model performance to include not only antecedent environmental factors but also their occurrence times in association with the dispersal phase of the life‐history stages (Kanno et al ).…”
Section: Discussionsupporting
confidence: 74%
“…In SDMs, they could reflect antecedent demographic and dispersal processes. In addition, the effects of environmental factors on a species distribution largely depend on the timing of their occurrence relative to the organism's life‐history strategy and stage (Winemiller , , Lytle and Poff , Amorim et al , George et al , Kanno et al ). Thus, considering both antecedent environmental conditions and their times of occurrence may be particularly important for understanding species distributions and thereby for improving SDMs.…”
mentioning
confidence: 99%
“…Following Kanno et al (2015Kanno et al ( , 2016bKanno et al ( , 2017, we used air temperature as a proxy for water temperature because heat exchange with air is the major physical driver of stream temperature (Mohseni and Stefan 1999, Morrill et al 2005, Letcher et al 2015a. We also used seasonal precipitation, often used as a proxy for streamflow, as a benchmark against which we compared mean and extreme streamflow covariates.…”
Section: Streamflow and Weather Datamentioning
confidence: 99%
“…For aquatic as well as terrestrial species, temporal variation in average annual and seasonal weather has been linked to changes in population abundance (Pardikes et al 2015, Kanno et al 2017, vital rates (Dybala et al 2013, Abadi et al 2017, and population dynamics (Seegrist and Gard 1972, Fern andez-Chac on et al 2011, Grossman et al 2016, Cleasby et al 2017. However, responses of animal populations may be more closely related to short-duration, high-magnitude extreme events or disturbances which exceed a biological threshold above or below which animals have reduced fitness (i.e., survival and reproductive success; Resh et al 1988, Lake 2003, Roland and Matter 2013, Childress and Letcher 2017.…”
Section: Introductionmentioning
confidence: 99%
“…; Kanno et al. ), have restricted Brook Trout to headwater tributaries in watersheds that are thought to have formerly harbored metapopulations. The overwhelming majority of these extant populations are restricted to small, isolated stream reaches with limited carrying capacity and little to no opportunity for genetic exchange with neighboring populations (see Whiteley et al.…”
mentioning
confidence: 99%